Mapping structural covariance networks in children and adolescents with post-traumatic stress disorder after earthquake - Mo, Xian; He, Meirong; Zhou, Lijun; Liu, Yunfei; Zhu, Hongru; Huang, Xiaoqi; Zeng, Guojun; Zhang, Junran; Li, Lingjiang (Frontiers in Psychiatry, 2022)
For children and adolescents, there is a high risk of developing post-traumatic stress disorder (PTSD) after suffering from catastrophic events. Previous studies have identified brain functionally and subcortical brain volumes structurally abnormalities in this population. However, up till now, researches exploring alterations of regional cortical thickness (CTh) and brain interregional structural covariance networks (SCNs) are scarce. In this cross-sectional study, CTh measures are derived from 3-Tesla Tl-weighted MRI imaging data in a well-characterized combined group of children and adolescents with PTSD after an earthquake(N=35) and a traumatized healthy control group(N=24). By using surface-based morphometry (SBM) techniques, the regional CTh analysis was conducted. To map interregional SCNs derived from CTh, twenty-five altered brain regions reported in the PTSD population were selected as seeds. Whole-brain SBM analysis discovered a significant thickness reduction in the left medial orbitofrontal cortex for the subjects with PTSD. Similarly, analysis of SCNs associated with 'seed' regions primarily located in default mode network (DMN), midline cortex structures, motor cortex, auditory association cortex, limbic system, visual cortex demonstrated that children and adolescents with PTSD are associated with altered structural covariance with six key regions. This study provides evidence for distinct CTh correlates of PTSD that are present across children and adolescents, suggesting that brain cortical abnormalities related to trauma exposure are present in this population, probably by driving specific symptom clusters associated with disrupted extinction recall mechanisms for fear, episodic memory network and visuospatial attention.